Standardized Preoperative Pathways Determining Preoperative Echocardiogram Usage Continue to Improve Hip Fracture Quality. (9th April 2022) - Esper, Garrett; Anil, Utkarsh; Konda, Sanjit; Furgiuele, David; Zaretsky, Jonah; Egol, Kenneth
Introduction: The purpose of this study was to assess the hospital quality measures and outcomes of operative hip fracture patients before and after implementation of an anesthesiology department protocol assigning decision for a preoperative transthoracic echocardiogram (TTE) to the hospitalist co-managing physician. Materials and Methods: Demographics, injury details, hospital quality measures, and outcomes were reviewed for a consecutive series of patients presenting to our institution with an operative hip fracture. In May of 2019, a new protocol assigning the responsibility to indicate a patient for preoperative TTE was mandated to the co-managing hospitalist at the institution. Patients were split into pre-protocol and post-protocol cohorts. Linear regression modeling and comparative analyses were conducted with a Bonferroni adjusted alpha as appropriate. Results: Between September 2015 and June 2021, 1002 patients presented to our institution and were diagnosed with a hip fracture. Patients in the post-protocol cohort were less likely to undergo a preoperative echocardiogram, experienced a shorter time (days) to surgery, shorter length of stay, an increase in amount of home discharges, and lower complication risks for urinary tract infection and acute blood loss anemia as compared to those in the pre-protocol cohort. There were no differences seen in inpatient or 30-day mortality. Multivariable linear regression demonstrated a patient's comorbidity profile (Charlson Comorbidity Index (CCI)) and their date of presentation (pre- or post-protocol), were both associated with (P<0.01) a patients' time to surgery. Conclusion: A standardized preoperative work flow protocol regarding which physician evaluates and determines which patients require a preoperative TTE allows for a streamlined perioperative course for hip fracture patients. This allows for a shortened time to surgery and length of stay with an increase in home discharges and was associated with a reduced risk of common index hospitalization complications including UTI and anemia.